Morbidity profile of children from birth to 18 years of age referred for intervention to the district early intervention centre in a District Hospital, Andhra Pradesh - Surendra Babu Darivemula; Khadervali Nagoor; K R John; P Shakeer Kahn; Chandra Sekhar Chittooru (Wolters Kluwer Medknow Publications, 2020)
Background: The "Child Health Screening and Early Intervention Services" program aims at early detection and management of the four dimensions prevalent in children-defects at birth, diseases in children, deficiency conditions, and developmental delays, including disabilities. Objective: The objective of the study was to assess the morbidity profile of children from birth to 18 years of age screened in the district early intervention center (DEIC). Methods: A record-based descriptive study was done in the DEIC in Chittoor, Andhra Pradesh. The data were retrieved for 1-year from April 2017 to March 2018 into the excel sheet, and the combined master sheet was prepared for analysis. The analysis was done with SPSS 21.0 Version. Results: A total of 10571 children were screened and referred to the DEIC during the period. Out of them, 5679 (53.7%) were male and 4892 (46.3%) were female. Among all the four types of morbidities screened, majority 4847 (45.9%) were having the childhood diseases, 4177 (39.5%) had developmental delays including disabilities, 1067 (10.1%) had different deficiencies, and 361 (3.4%) had birth defects. Among the adolescent health issues, 119 (1.1%) were screened and sent for the early intervention to the district hospital. Conclusions: A huge number of children were screened and referred to the DEIC every year for intervention. The health sector has to focus more on the resources like workforce, training of peripheral health workers at regular intervals about the different morbidities screened, that would help in identifying the morbidities at the earliest possible time and receive the intervention at the best center.